KAJIAN PENGEMBANGAN SAPI POTONG: IDENTIFIKASI CIRI SISTEM PRODUKSI SAPI POTONG DI PEDESAAN A BEEF-CATTLE DEVELOPMENT ASSESSMENT: IDENTIFICATION OF PRODUCTION SYSTEM CHARACTERISTIC OF BEEF-CATTLE IN RURAL AREA - Sodiq, Akhmad; Setianto, Novie Andri (Pembangunan Pedesaan, 2007)
The objective of this study was to identify the production system characteristic of beef-cattle in rural areas. On-farm survey in four provinces of Indonesia, i.e., East-Java, Bali, West Nusa Tenggara, and West Sumatra by purposive sampling method based on livestock production system was applied in this study. Assessment focus on (1) keeping objectives, (2) farm size, (3) breed preference, (4) reproduction and matting system, and (5) husbandry practices was identified and presented in this paper.